4G LTE Network Quality Comparison Provider Telkomsel and Tri in Pariaman City - Irvandito Pondria; Miftahul Hamdi; Afrizal Yuhanef; Dikky Chandra (International Journal of Wireless And Multimedia Communications, 2025)
Along with the development of the current era of globalization, human needs for telecommunications are also increasing, especially in the telecommunications sector. A technology called Long Term Evolution (LTE) was introduced, which is a fourth generation (4G) cellular network technology. LTE is capable of providing data transfer speeds of up to 100 Mbps on the downlink side and 50 Mbps on the uplink side. The growth in the number of telecommunications service users in Pariaman City has caused a decline in network quality, especially 4G LTE technology. Benchmarking (Comparison) of the quality of 4G LTE operator services is carried out by measuring, comparing, and analyzing the network quality (performance) of two 4G LTE operators in Pariaman City. The measurement process uses the drive test method with the G-Net Track Pro application to measure RSRP, RSRQ, SINR and Throughput in Pariaman City. The comparison results were obtained in Pariaman City for Telkomsel operators having network quality parameters RSRP with a percentage of 48.71%, RSRQ with a percentage of 61.11%, SINR with a percentage of 84.25% and Throughput with a percentage of 68.48% while Tri operators have RSRP values with a percentage of 59.74%, RSRQ with a percentage of 50.38%, SINR with a percentage of 85.68% and Throughput with a percentage value of 66.63%. In general, it can be concluded that Tri operators are included in the good category in terms of signal quality and integrity while Telkomsel operators are in the good category in terms of Coverage.